(untitled) (Global Journals of Research in Engineering, 2013)
The term Levitation refers to a class of technologies that uses magnetic levitation to propel vehicles with magnets rather than with wheels axles and bearings Maglev derived from magnetic levitation uses magnetic levitation to propel vehicles With maglev a vehicle is levitated a short distance away from a guide way using magnets to create both lift and thrust High-speed maglev trains promise dramatic improvements for human travel widespread adoption occurs Maglev trains move more smoothly and somewhat more quietly than wheeled mass transit systems Their nonreliance on friction means that acceleration and deceleration can surpass that of wheeled transports and they are unaffected by weather The power needed for levitation is typically not a large percentage of the overall energy consumption Most of the power is used to overcome air resistance drag Although conventional wheeled transportation can go very fast maglev allows routine use of higher top speeds than conventional rail and this type holds the speed record for rail transportation Vacuum tube train systems might hypothetically allow maglev trains to attain speeds in a different order of magnitude but no such tracks have ever been built Compared to conventional wheeled trains differences in construction affect the economics of maglev trains